2014
DOI: 10.1111/jpi.12177
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes osteoblast differentiation and mineralization of MC3T3‐E1 cells under hypoxic conditions through activation of PKD/p38 pathways

Abstract: Osteoblastic differentiation and bone-forming capacity are known to be suppressed under hypoxic conditions. Melatonin has been shown to influence cell differentiation. A number of in vitro and in vivo studies have suggested that melatonin also has an anabolic effect on bone, by promoting osteoblastic differentiation. However, the precise mechanisms and the signaling pathways involved in this process, particularly under hypoxic conditions, are unknown. This study investigated whether melatonin could promote ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 45 publications
3
49
1
Order By: Relevance
“…Recently, an in vitro study demonstrates that melatonin promotes differentiation and mineralization of cultured osteoblast cells (MC3T3-E1 cells) under hypoxic conditions [145]. Thus this study concludes that melatonin promotes osteoblastic differentiation of MC3T3-E1 cells under hypoxic conditions via the p38 Mapk and Prkd1 signaling pathways.…”
Section: Melatonin In Bone Diseasementioning
confidence: 68%
“…Recently, an in vitro study demonstrates that melatonin promotes differentiation and mineralization of cultured osteoblast cells (MC3T3-E1 cells) under hypoxic conditions [145]. Thus this study concludes that melatonin promotes osteoblastic differentiation of MC3T3-E1 cells under hypoxic conditions via the p38 Mapk and Prkd1 signaling pathways.…”
Section: Melatonin In Bone Diseasementioning
confidence: 68%
“…A study by Son, using MC3T3 cells cultured in media containing melatonin at concentrations between 10 and 250 µM. quantified gene expression of ALP , COLIA1 , OCN , and OSX after 1, 3, 7, and 14 days of cell culture showed that gene expression increased in dose and time-dependent manner [46]. However, a study by Nakade using human osteoblast cells and the addition of melatonin to the cell culture media at concentration between 5 and 100 µM, measured different markers of osteoblast differentiation after four days of cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ) is one of the most widely used housekeeping genes for managing and normalizing the expression of other genes [7,15,17,20,30,46]. …”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms by which melatonin regulates the bone environment is through its stimulatory effect on osteoblasts 33, 34 . A previous study revealed that melatonin enhances the differentiation of human adult mesenchymal stem cells into mature osteoblasts via MT2 melatonin receptors 35 , and that, during osteoblast differentiation, treatment with melatonin increases the expression levels of osteocalcin (OC), a late, highly specific osteoblast marker of bone formation, followed by enhanced bone mineralization of MC3T3-E1 cells 36 . Although it has been reported that melatonin promotes the expression of Runx2, a master transcription factor during the early stage of osteogenesis 37 , the precise mechanism by which it regulates the differentiation of preosteoblasts into mature osteoblasts remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an intraperitoneal administration of melatonin slightly enhanced new cortical bone formation in the femurs of mice 19 . In addition, melatonin promoted mineralization and osteoblastic differentiation by enhancing the expression of Runx2, which is a key transcription factor in the early stage of osteogenic differentiation, via the mitogen-activated protein kinase (MAPK) signaling pathway 20 .…”
Section: Introductionmentioning
confidence: 99%